Developing a Discovery Learning-Based E-Module Supported by Instagram to Enhance Students’ Learning Motivation - Rahmania Rahman; Muhammad Fuad; Risqah Amaliah Kasman (Cerdas: Jurnal Ilmu Pendidikan Sosial dan Humaniora, 2025)
This study was motivated by the low learning motivation of students in reproductive system topics in Grade XI of senior high school, which is attributed to conventional teaching approaches and the lack of interactive digital teaching materials. The reproductive system is often perceived as abstract and sensitive, thus requiring an innovative learning strategy. This research aimed to develop a valid, practical, and effective Discovery Learning-based e-module on the reproductive system supported by Instagram to enhance students’ learning motivation. The method employed was Research and Development (R&D) using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The trial involved 32 students from class XI MIA 2 at SMA Negeri 1 Barru. Instruments included validation sheets, teacher and student response questionnaires, and a learning motivation questionnaire. The validation results indicated that the e-module and its supporting instruments were in the "very valid" and "very feasible" categories, with average scores above 3.75. Teachers rated the practicality of the e-module at 88.39% (very practical category). Its effectiveness was demonstrated by an increase in learning motivation from 56.38% to 84%, with an average N-Gain score of 0.58 (moderate category). Significant improvements were also observed in indicators such as students’ interest in solving problems (36.40%) and their enthusiasm for expressing and defending opinions (39.82%). Therefore, the Discovery Learning-based e-module on the reproductive system supported by Instagram effectively enhanced students’ motivation and is well-suited to the characteristics of today’s digital-native learners.